Effect of heating and electric conductivity of anthocyanin extract from red dragon fruit (Hylocereus polyrhizus) as a sensitizer material. Issue 1 (January 2021) - Iqbal,; Basir Cyio, M; Darwis, D
Abstract: Research on the Effect of Heating and Electrical Conductivity of Anthocyanin Extract from Red Dragon Fruit ( Hylocereuz Polyrhizus ) as a sensitizer has been conducted. Red dragon fruit ( Hylocereuz polyrhizus ) was macerated extracted with a solvent ratio of 1: 2. The absorbance was measured at a wavelength of 300 - 700 nm using a UV-Vis spectrometer with a dilution of 25 times. Extract stability test due to heating was carried out at temperatures of 40°C, 50 °C, 60 °C, 65 °C, 70 °C and 80 °C. The results showed that heating temperature causes a decrease of absorption, the sensitizer material of extract was unstable at high temperatures ranging from 70 °C and above, it was observed with the occurrence of color changes and the wavelength and absorbance were not measured. The electrical conductivity in bright conditions of the extract also decreased due to the effect of heating. Electrical conductivity in bright conditions Anthocyanin extract at temperatures: 32 °C, 40 °C, 50 °C, 60 °C, 70 °C, and 80 °C are 1569 μS/cm, at 493 μS/cm, 592 μS/cm, 526 μS/cm, 474 μS/cm, 544 μS/cm, 494 μS/cm respectively.